A Theoretical Literature Review on the Social Identity Model of Organizational Leadership. Issue 3 (August 2019) - Turner, John R.; Chacon-Rivera, Martin R.
The Problem: Leadership is commonly represented as being an individual construct with characteristics, competencies, and traits that identify the individual. Leadership development interventions are also framed around the individual leader. Leadership needs to account for the perceptions and identities of all group members. This includes a leader who is a prototype of both the in-group and out-group members. The Solution: Leadership development efforts could be designed to account for the different identities of all members involved, producing a representative prototypical leader. Implementing the social identity model of organizational leadership (SIMOL) theory could be the catalyst that furthers human resource development (HRD)'s efforts of providing a new Worldview of Leadership as called for by McLean and Beigi, one that is all inclusive of its membership. The Stakeholders: Considering the SIMOL theory, HRD scholars and scholar-practitioners could offer new perspectives when viewing the leader-group dynamics and leadership development.